SOCIAL DYNAMICS OF TUBANG KARUEI VILLAGE LIFE IN MIGRATION TRADITION AND AFTER DETERMINATION A Cultural Anthropology Studies - Septriani Septriani; Tomi Arianto (eScience Humanity Journal, 2021)
The paper aimed to explore the transformation of community traditions in Tubang Karuei village from migrating to settling down. The Dayak Ot-Danum people of Central Kalimantan have a tradition of migrating from generation to generation, due to various factors. Currently, this tradition is no longer being practiced and they have settled in an area called the village. The process of settling the Dayak Ot-Danum community of Tumbang Karuei Village is a result of the company's efforts to secure its concession area. The results of this study indicate that this transformation has a correlation with the development policies and economic growth proclaimed by the New Order government. In order to carry out the program, the company must draw clear boundaries between the communal rights area and the concession area. Efforts to fix this area are not carried out by force and coercion but run through compromise, persuasion and good communication. The company, through its CSR program, also has a huge impact on the local community, which then results in economic diversification, health improvement, education, etc. This further reduces the negative points of the area of ​​origin and the positive points of the destination so that migrating is no longer the right choice.